THERMODYNAMIC ANALYSIS OF ALKALINE ELECTROLYSIS UNDER VISIBLE LIGHT ILLUMINATION: COMPARATIVE ASSESSMENT OF GREEN AND BLUE LED EXPOSURE - Santoso, Mardi; Ahmad, Anton Royanto; Sinurat, David Fernando; Hamidi, Nurkholis; Purnami (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This study explores the thermodynamic behavior of alkaline electrolysis under visible light illumination, focusing on the effects of green and blue wavelengths in the absence of chemical additives. Through a series of controlled experiments, temperature evolution, energy input, and thermal efficiency were analyzed over a 20-minute electrolysis period. Results show that both green and blue light enhance the system's thermal response compared to dark (control) conditions, with blue light achieving the highest temperature rise and energy conversion efficiency. Arrhenius analysis revealed a clear temperature dependence of the rate constant, and strong correlations were observed between temperature rise (ΔT), heat energy (Q), and system efficiency. These findings suggest that visible light particularly blue light can significantly improve the thermal dynamics of electrolysis systems, paving the way for low-cost, passive solar-assisted hydrogen production.